1998
DOI: 10.1212/wnl.51.2.418
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of stroke outcome with echoplanar perfusion- and diffusion-weighted MRI

Abstract: Combined early PI and DWI can define different acute infarct patterns, which may allow the selection of rational therapeutic strategies based on the presence or absence of potentially salvageable ischemic tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

27
387
7
3

Year Published

1999
1999
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 508 publications
(424 citation statements)
references
References 16 publications
27
387
7
3
Order By: Relevance
“…Mean volumes were 38 Ϯ 46 cm 3 at day 0, 69 Ϯ 72 cm 3 at day 1, and 57 Ϯ 66 cm 3 at day 60. Mean volumes for patients with arterial recanalization were 31 Ϯ 41 cm 3 , 51 Ϯ 61 cm 3 , and 41 Ϯ 58 cm 3 , respectively. Those for patients without arterial recanalization were 50 Ϯ 54 cm 3 , 100 Ϯ 82 cm 3 , and 86 Ϯ 72 cm 3 at day 60.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mean volumes were 38 Ϯ 46 cm 3 at day 0, 69 Ϯ 72 cm 3 at day 1, and 57 Ϯ 66 cm 3 at day 60. Mean volumes for patients with arterial recanalization were 31 Ϯ 41 cm 3 , 51 Ϯ 61 cm 3 , and 41 Ϯ 58 cm 3 , respectively. Those for patients without arterial recanalization were 50 Ϯ 54 cm 3 , 100 Ϯ 82 cm 3 , and 86 Ϯ 72 cm 3 at day 60.…”
Section: Resultsmentioning
confidence: 99%
“…How- ever, the ischemic penumbra is a time-dependent dynamic concept, with lesion growth from the center to the periphery and recruitment of tissue at risk into the infarct (21,23). Thus, the mismatch (and thus, inversely, the DWI growth) became the target of stroke therapeutics to evaluate the salvageable tissue (3,24,25). The mismatch model assumes that the initial diffusion lesion represents irreversibly infarcted core tissue.…”
Section: Discussionmentioning
confidence: 99%
“…PWI shows the relative latency of arrival and clearance of blood flow to each voxel of the image. Areas of tissue with a time to peak arrival of contrast of > 4 seconds delay, relative to the homologous region in the contralesional hemisphere, are areas that may be getting enough blood to survive, but not enough to function correctly and can be considered "hypoperfused" (Barber, et al, 1998;Butcher et al, 2005;Hillis et al, 2001b). Therefore, tissue areas of dense ischemia and/or hypoperfusion can be considered dysfunctional.…”
mentioning
confidence: 99%
“…Salvageable tissue in the ischemic penumbra is present in many patients well beyond 3 hours, perhaps even up to 24 or 48 hours. 8,9 The clinical results are supported by Phase II imaging studies such as our Echoplanar Imaging Thrombolytic Evaluation Trial (EPITHET) trial, which showed the biological benefits of tPA at 3 to 6 hours in patients with perfusion-diffusion mismatch on MRI with significantly increased reperfusion, strong trends to infarct growth attenuation, and improved clinical outcomes. 10 There are many important questions for the reperfusion field that need to be addressed.…”
mentioning
confidence: 94%